Applications of Machine Learning in Big-Data Analytics and Cloud Computing - Pani, Subhendu Kumar (River Publishers Series in Information Science and Technology Ser., 2021)
This book introduces the state-of-the-art trends and advances in the use of Machine Learning in Cloud and Big Data Analytics. The book will serve as a reference for Data Scientists, systems architects, developers, new researchers and graduate level students in Computer and Data Science. The book will describe the concepts necessary to understand current Machine Learning issues, challenges and possible solutions as well as upcoming trends in Big Data Analytics.